Draft Genome of the Common Snapping Turtle, Chelydra serpentina, a Model for Phenotypic Plasticity in Reptiles. Issue 12 (1st December 2020) - Das, Debojyoti; Singh, Sunil Kumar; Bierstedt, Jacob; Erickson, Alyssa; Galli, Gina L J; Crossley, Dane A; Rhen, Turk
Abstract: Turtles are iconic reptiles that inhabit a range of ecosystems from oceans to deserts and climates from the tropics to northern temperate regions. Yet, we have little understanding of the genetic adaptations that allow turtles to survive and reproduce in such diverse environments. Common snapping turtles, Chelydra serpentina, are an ideal model species for studying adaptation to climate because they are widely distributed from tropical to northern temperate zones in North America. They are also easy to maintain and breed in captivity and produce large clutch sizes, which makes them amenable to quantitative genetic and molecular genetic studies of traits like temperature-dependent sex determination. We therefore established a captive breeding colony and sequenced DNA from one female using both short and long reads. After trimming and filtering, we had 209.51Gb of Illumina reads, 25.72Gb of PacBio reads, and 21.72 Gb of Nanopore reads. The assembled genome was 2.258 Gb in size and had 13, 224 scaffolds with an N50 of 5.59Mb. The longest scaffold was 27.24Mb. BUSCO analysis revealed 97.4% of core vertebrate genes in the genome. We identified 3.27 million SNPs in the reference turtle, which indicates a relatively high level of individual heterozygosity. We assembled the transcriptome using RNA-Seq data and used gene prediction software to produce 22, 812 models of protein coding genes. The quality and contiguity of the snapping turtle genome is similar to or better than most published reptile genomes. The genome and genetic variants identified here provide a foundation for future studies of adaptation to climate.